2007
DOI: 10.1007/s10853-007-1661-3
|View full text |Cite
|
Sign up to set email alerts
|

Laser melting functionally graded composition of Waspaloy® and Zirconia powders

Abstract: An approach for fabricating functionally graded specimens of supernickel alloy and ceramic compositions via Selective Laser Melting (SLM) is presented. The focus aimed at using the Functionally Graded Material (FGM) concept to gradually grade powdered compositions of Zirconia within a base material of Waspaloy ® . A high power Nd:YAG laser was used to process the material compositions to a high density with gradual but discrete changes between layered compositions. The graded specimens initially consisted of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(37 citation statements)
references
References 31 publications
0
36
0
1
Order By: Relevance
“…Liu et al [8] reported that they could fabricate crack free Ti-TiC FGMs by varying 0 to 95 vol% TiC using LENS™. Mumtaz and Hopkinson [9] reported that local heat transfer conditions affect porosity within the YSZ-Waspalloy FGM made by Selected Laser Melting technique. Unocic et al [10] studied the effect of LENS process parameters on dilution and hence compositional variation in FGMs.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [8] reported that they could fabricate crack free Ti-TiC FGMs by varying 0 to 95 vol% TiC using LENS™. Mumtaz and Hopkinson [9] reported that local heat transfer conditions affect porosity within the YSZ-Waspalloy FGM made by Selected Laser Melting technique. Unocic et al [10] studied the effect of LENS process parameters on dilution and hence compositional variation in FGMs.…”
Section: Introductionmentioning
confidence: 99%
“…There are various types of SFF innovations, even so, the laser based forms are mostly utilized in creating functional graded material [6]. Laser based SFF process for FGM [7] include: (i) laser cladding based strategy [8,9], and (ii) Selective Laser Sintering (SLS) [10,11]. SFF includes five essential steps [12].…”
Section: Solid Free Form (Sfm) Fabrication Methodsmentioning
confidence: 99%
“…Some researchers have tried to make FGM with present systems (116)(117)(118). Beal et al tried to make a tool by changing the proportion of materials (copper and tool steel), which is the most used material in tooling.…”
Section: Functionally Graded Materialsmentioning
confidence: 99%